A framework for exploring counselors' anti-queer biases - Scoville, Diane (My University, 2002)
Despite practice standards and ethical guidelines that direct otherwise, counselors continue to maintain anti-queer biases and practice in discriminatory ways with queer clients. This dissertation offers a framework for exploring and understanding anti-queer biases and behaviors. Psychoanalytic, philosophical, and queer discourses are engaged and extended to investigate the ways in which personal and cultural influences co-constitute gender and sexual identities, individual subjectivity, and relationality as they relate to counselors' anti-queer biases. Implications for counseling professionals are included.
Thesis (Ph. D.)--University of Washington, 2002
Keywords: Theses--Education